1972
DOI: 10.1128/iai.6.4.465-468.1972
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus hominis Type 2 Infections in Rabbits: Effect of Prior Immunization with Attenuated Mycobacterium bovis (BCG) Cells

Abstract: Angora, New Zealand, and Dutch-belted rabbits were tested for their susceptibility to graded doses of Herpesvirus hominis type 2 administered by vaginal instillation, intracorneal injection, and scarification of the cornea. Central nervous system involvement and death occurred after infection by the various routes employed. Prior immunization of Dutch-belted and New Zealand rabbits with viable Mycobacterium bovis (BCG) cells injected intravenously provided protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…treated mice might play a major role in resistance. In contrast with our results, Larson et al (20) and Lodmell and Ewalt (21) reported that the interferon was not detected in sera of Mycobacterium tuberculosisor BCG-treated mice after virus inoculation, and they suggested that the importance of systemic interferon in enhanced resistance of these mice to virus infection was doubtful. These discrepancies may reflect the doses of virus inoculated or the different target organs for the virus used.…”
Section: Discussioncontrasting
confidence: 99%
“…treated mice might play a major role in resistance. In contrast with our results, Larson et al (20) and Lodmell and Ewalt (21) reported that the interferon was not detected in sera of Mycobacterium tuberculosisor BCG-treated mice after virus inoculation, and they suggested that the importance of systemic interferon in enhanced resistance of these mice to virus infection was doubtful. These discrepancies may reflect the doses of virus inoculated or the different target organs for the virus used.…”
Section: Discussioncontrasting
confidence: 99%
“…[BCG]) (9,76,140) and Staphylococcus aureus (133), and nonviable microbial preparations, such as staphylococcal phage lysate (133,140) and typhoid and Brucella vaccines (140), have been used, as well as synthetic compounds, such as levamisole, an anthelmintic drug (140). Macrophage transfer.…”
Section: Modulations Of the Function Of Thementioning
confidence: 99%
“…Effects of nonspecific immunity induced by BCG vaccination, passive administration of SAS, and a combination of these procedures upon the course of vaginal HVH2 infections. The feasibility of infecting adult female mice vaginally with HVH2 (as indicated above) and the data of other workers showing the importance of both cell-mediated immunity (9,13,19,20) and specific antibody (4,14) in controlling HVH infections were used as the basis of the following experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the severe discomfort experienced by patients, the devastating effects of neonatal infections and the possible role of vaginal herpetic infections in cervical cancer have aroused further interest in these agents (15)(16)(17)(18). Investigations in rabbits (13), humans (1), and mice (14,19) have established the important role of cell-mediated immunity in the control of herpes infections. It has been observed that although the sera of patients with recurrent herpetic lesions frequently contain specific neutralizing antibody, these antibodies alone do not prevent recurrence of the disease.…”
mentioning
confidence: 99%